2020
DOI: 10.1177/0363546520907914
|View full text |Cite
|
Sign up to set email alerts
|

Safer and Cheaper: An Enhanced Milestone-Based Return to Play Program After Anterior Cruciate Ligament Reconstruction in Young Athletes Is Cost-Effective Compared With Standard Time-Based Return to Play Criteria

Abstract: Background: Safe return to play (RTP) after anterior cruciate ligament (ACL) reconstruction is critical to patient satisfaction. Enhanced rehabilitation after ACL reconstruction with appropriate objective criteria for RTP may reduce the risk of subsequent injury. The cost-effectiveness of an enhanced RTP (eRTP) strategy relative to standard post-ACL reconstruction rehabilitation has not been investigated. Purpose: To determine if an eRTP strategy after ACL reconstruction is cost-effective compared with standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…This observed lack of formal postoperative functional testing during UCLR rehabilitation stands in stark contrast to the anterior cruciate ligament reconstruction (ACLR) literature, in which numerous functional assessment tools have been devised and studied, such as hop testing, the running t test, KT-1000 arthrometry, dynamometer strength testing, isokinetic testing, and postural control analysis. 9,25,39 While successful progression through a return-to-throwing program without pain can serve as a crude functional assessment, athletes may downplay discomfort or alter their throwing mechanics in an attempt to expedite RTC. As the utilization of UCLR continues to increase, there is a growing need for validated methods of assessing functional recovery of not only the upper extremity but also the entire kinetic chain, including the core and lower extremities.…”
Section: Discussionmentioning
confidence: 99%
“…This observed lack of formal postoperative functional testing during UCLR rehabilitation stands in stark contrast to the anterior cruciate ligament reconstruction (ACLR) literature, in which numerous functional assessment tools have been devised and studied, such as hop testing, the running t test, KT-1000 arthrometry, dynamometer strength testing, isokinetic testing, and postural control analysis. 9,25,39 While successful progression through a return-to-throwing program without pain can serve as a crude functional assessment, athletes may downplay discomfort or alter their throwing mechanics in an attempt to expedite RTC. As the utilization of UCLR continues to increase, there is a growing need for validated methods of assessing functional recovery of not only the upper extremity but also the entire kinetic chain, including the core and lower extremities.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 9 Historically, there was a movement toward accelerated rehabilitation and earlier return to play, but this was based largely on lower-level evidence. DeFrancesco et al 8 proposed that enhanced rehabilitation, which includes additional neuromuscular training, advanced testing, and follow-up physician visits as compared with standard rehabilitation, is cost-effective based on a reduction in subsequent ACL injuries. To date, the optimal method of determining an athlete’s readiness to RTS is unknown and should be based on a patient’s physical function and the biologic factors that affect graft healing.…”
Section: Discussionmentioning
confidence: 99%
“…The high rates of complication found here further support the use of prevention programs and formal return-to-play programs, as previous research has shown that their value increases with the likelihood of subsequent injury. 2,9 We recognize that techniques in pediatric ACLR continue to evolve-the senior author (T.J.G.) now almost exclusively uses quadriceps tendon autograft with cortical button fixation-which may limit the generalizability of our findings to current patients.…”
Section: Resultsmentioning
confidence: 99%